2016
DOI: 10.18632/oncotarget.13635
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequences within glioma-derived extracellular vesicles can cross the intact blood-brain barrier and be detected in peripheral blood of patients

Abstract: Tumor-cell-secreted extracellular vesicles (EVs) can cross the disrupted blood-brain barrier (BBB) into the bloodstream. However, in certain gliomas, the BBB remains intact, which might limit EVs release. To evaluate the ability of tumor-derived EVs to cross the BBB, we used an orthotopic xenotransplant mouse model of human glioma-cancer stem cells featuring an intact BBB. We demonstrated that all types of tumor cells-derived EVs−apoptotic bodies, shedding microvesicles and exosomes−cross the intact BBB and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(175 citation statements)
references
References 34 publications
2
171
0
2
Order By: Relevance
“…65 Despite the association between BBB dysfunctions and GBM disease progression, EVs derived from glioma cells were shown to cross the intact BBB and were detected in the blood of GBM patients. 66 This highlights the importance of EVs in liquid biopsies since EVs can be detected in cases in which the BBB is not compromised.…”
Section: Current Approaches To the Management Of Gbm Diagnosismentioning
confidence: 93%
“…65 Despite the association between BBB dysfunctions and GBM disease progression, EVs derived from glioma cells were shown to cross the intact BBB and were detected in the blood of GBM patients. 66 This highlights the importance of EVs in liquid biopsies since EVs can be detected in cases in which the BBB is not compromised.…”
Section: Current Approaches To the Management Of Gbm Diagnosismentioning
confidence: 93%
“…Importantly, the use of EVs as therapeutic vectors presents several advantages, at least on paper, such as the fact that they can be isolated from the blood of the same patient, thus being immunologically compatible. Moreover, exosomes are distributed throughout the body, even being able to cross the intact blood‐brain barrier . In addition, in some cases, such as the exosomes released by mesenchymal stem cells (MSCs), they possess intrinsic therapeutic potential, akin to that of MSCs themselves, by being immunomodulatory and inducing tissue regeneration .…”
Section: Exosomes As Therapy For Diabetesmentioning
confidence: 99%
“…García-Romero et al [123] showed that glioma-derived EVs such as exosomes and apoptotic bodies can be detected in peripheral blood and that they carry the relevant glioma-specific DNA mutations, such as AKT3, CDK4, CDKN2A, EGFR, ERBB2, IDH1/2, MDM2, PTEN and TP53. This study showed that exoDNA reflects crucial DNA alterations of the exosome releasing tumors.…”
Section: Application Of Exodna Analysis In Neuropathologymentioning
confidence: 99%
“…In the context of glioma diagnostics, IDH mutations are of special interest as they predominantly occur in diffuse and anaplastic glioma as well as in secondary glioblastoma. By analysis of exosomes, these characteristic IDH mutations may be detectable, both at the DNA and at the RNA levels [123,130]. The MGMT promoter methylation is of crucial importance for therapy planning in glioma patients.…”
Section: Application Of Exodna Analysis In Neuropathologymentioning
confidence: 99%